2018
DOI: 10.1111/jpc.14167
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety‐related disorders: An overview

Abstract: Anxiety‐related disorders are common in the child and adolescent population. They cause significant distress, which can affect social, emotional, family and academic functioning. They frequently present in general paediatric and primary care settings. Comprehensive assessment should include the child as well as parent and family functioning because anxiety‐related disorders in other family members are common and, if untreated, can affect outcomes for the child. There are good evidence‐based psychological inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Anxiety disorders are the most prevalent mental disorders and are associated with immense social health care costs 21 . A central symptom is avoidance behavior, which also acts as a reinforcer of the anxious state 24, 38 . It is vital then to understand the underlying cellular and circuitry mechanisms underpinning this type of avoidance behavior, which could result in new methods to break the cycle of anxiety-avoidance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anxiety disorders are the most prevalent mental disorders and are associated with immense social health care costs 21 . A central symptom is avoidance behavior, which also acts as a reinforcer of the anxious state 24, 38 . It is vital then to understand the underlying cellular and circuitry mechanisms underpinning this type of avoidance behavior, which could result in new methods to break the cycle of anxiety-avoidance.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is PV GABAergic interneurons, which comprise only 3-4% of all neurons in the NAc 19, 20 . In other brain regions, these neuron regulate fear response 21 , anxiolysis 22 , alcohol addiction 23 , and reward seeking 3, 24 . However, we know less about the function of accumbal PV neurons and the inputs they receive, and nothing about any possible role in anxiety related behavior.…”
Section: Introductionmentioning
confidence: 99%
“…For moderate to severe ADHD, depression and any psychosis, medication should be considered a first‐line intervention in combination with psychosocial management. Pharmacotherapy is indicated for anxiety where psychosocial interventions have been ineffective …”
Section: Management Of Aggression In Childrenmentioning
confidence: 99%
“…Pharmacotherapy is indicated for anxiety where psychosocial interventions have been ineffective. 30,31 For the management of aggression, studies have shown that atypical antipsychotics (risperidone and aripiprazole), α-2 adrenergic agonists (clonidine and guanficine) and mood stabilisers (lithium and valproate) are all more effective than placebo for reducing aggression in children with conduct disorder. 30 However, all of these medications carry considerable early and later adverse effects.…”
Section: Management Of Aggression In Childrenmentioning
confidence: 99%
“…Comorbidities may affect treatment response and should be actively co-managed. There are documented increases in the incidence of separation anxiety, specific phobias, generalised anxiety 24 , attention-deficit hyperactivity disorder 25 and oppositional defiant disorder in children with soiling. 26 The Avon longitudinal study has been helpful in identifying trajectories and associations with soiling, albeit with the bias associated with relying on maternal report.…”
Section: Treatment Resistance and Comorbiditiesmentioning
confidence: 99%